Barriers and facilitators to obesity prevention dissemination and implementation efforts in the childcare centre setting from the provider perspective. (3rd February 2020) - Lebron, Cynthia N.; Ofori, Ashley; Sardinas, Krystal; Luaces, Maria; Natale, Ruby; Messiah, Sarah E.
Abstract: Background: It has been established that the childcare centre (CCC) is a setting suitable for healthy weight promotion efforts. As the field advances, it is important to understand the barriers and facilitators to early childhood obesity prevention implementation and dissemination efforts from the CCC providers' perspective. This is especially true among those who serve low‐income and diverse populations to maximize scalability success. Methods: Focus groups were held in English or Spanish with CCC providers across six CCCs who implemented healthy caregivers–healthy children (HC2), an early childhood healthy weight promotion programme targeting 2‐ to 5‐year‐olds from low‐resource backgrounds. Centres represented both rural and urban environments. Focus groups were audio recorded, transcribed, and coded. A thematic analysis that combined a deductive and inductive approach was conducted. Codes were analysed using Dedoose to identify general themes and subthemes. Results: CCC providers stated that (a) children understood the nutritional benefits of healthy foods; (b) improved cognitive development as a result of HC2; (c) parents were barriers to HC2 implementation efforts, particularly in terms of cooperative healthy lifestyle efforts; and (d) modelling healthy eating and making healthy CCC environmental changes facilitated HC2 implementation. Overall, HC2 was well received by CCC teachers, and they shared creative classroom HC2 adaptions and improvements. Conclusions: CCC providers can provide valuable insight to guide early childhood healthy weight promotion programme dissemination and implementation efforts. Although they value the implementation of HC2 programme in their classroom settings, they perceive parents as somewhat obstructive. This information is critical to informing future healthy weight promotion efforts in this setting, especially among low‐resource families. It is important to continue to include the CCC provider viewpoint in future obesity prevention efforts to maximize scalability and sustainability efforts.